Preparation method and application of aqueous zinc ion battery negative electrode protection anti-shedding coating

By constructing a protective coating composed of organic acid and sodium citrate in situ on the zinc negative electrode of the aqueous zinc ion battery, the problems of zinc dendrites growth, electrolyte corrosion and hydrogen evolution are solved, and the cycle life and stability of the battery are significantly improved. .

CN119419276APending Publication Date: 2025-02-11ZHEJIANG UNIV OF TECH SHENGZHOU INNOVATION RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411550790.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The zinc negative electrode of aqueous zinc ion batteries has uncontrollable zinc dendrites growth, electrolyte corrosion and hydrogen evolution, resulting in low circulation efficiency and limited life.

Method used

Organic acid + sodium citrate is used as the main raw materials, and a protective shed-resistant coating is built on zinc sheets in situ based on the 'etch-nucleation growth' mechanism to ensure the stability and protection effect of the coating structure.

Benefits of technology

This coating is not easy to fall off, can effectively inhibit the formation of zinc dendrites, improve the circulation life of zinc negative electrodes, and maintain a stable structure and protective effect during the battery cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419276A_ABST
    Figure CN119419276A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of an aqueous zinc ion battery negative electrode protection anti-shedding coating. The preparation method comprises the following steps: step 1, alternately cleaning a zinc sheet with hydrochloric acid and absolute ethyl alcohol; 2, mixing and stirring sodium citrate and an organic acid solution to obtain a blended solution; 3, stirring and heating the blended solution, and carrying out a cross-linking reaction to obtain a viscous solution; and 4, coating the viscous solution on the surface of a zinc sheet, and after reaction, cleaning and drying to prepare the aqueous zinc ion battery negative electrode with a protective anti-falling coating on the surface. According to the invention, organic acid and sodium citrate are used as main raw materials, and a protective anti-shedding coating is constructed in situ on a zinc sheet based on an etching-nucleation growth mechanism. The coating is good in structural stability, not prone to falling off and good in zinc negative electrode protection effect, and zinc ions can be guided to be evenly deposited on the surface of the zinc negative electrode, so that formation of dendritic crystals is inhibited, and the cycle life of the zinc negative electrode is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and more specifically relates to a preparation method and application of a negative electrode protective detachment-resistant coating for an aqueous zinc ion battery. Background Art

[0002] With the depletion of traditional fossil fuels and the intensification of environmental pollution, renewable energy (solar energy, geothermal energy, wind energy, etc.) has attracted great attention. Energy storage systems are expected to achieve large-scale application of renewable energy. Among many rechargeable batteries, aqueous zinc-ion batteries have high safety, high theoretical specific capacity (820mAh g -1 and 5585mAh cm 3 ), low redox potential (0.76 V compared to the standard hydrogen electrode), low cost, abundant reserves and environmental friendliness of the zinc metal negative electrode. Therefore, aqueous zinc-ion batteries are expected to shine in energy storage as a low-cost, environmentally friendly and safe new energy storage system.

[0003] However, there are still three key problems in the zinc negative electrode of aqueous zinc-ion batteries: uncontrollable zinc dendrite growth, electrolyte corrosion and hydrogen evolution. The uneven distribution of electric field on the surface of the zinc negative electrode produces a tip effect that makes the Zn 2+ Uneven deposition. As the battery cycle continues, zinc dendrites gradually form, causing a large amount of zinc to be exposed to the electrolyte and corroded, thereby accelerating the hydrogen evolution reaction. In addition, zinc dendrites will pierce the diaphragm and reach the positive electrode, causing an internal short circuit. The interaction of the above three problems leads to low cycle efficiency and limited life of aqueous zinc-ion batteries. In order to solve the above problems, researchers have proposed many strategies, such as electrolyte optimization, 3D negative electrode structure construction, zinc negative electrode surface modification and diaphragm modification. Among them, zinc negative electrode surface modification is one of the most effective methods. The current zinc negative electrode surface modification mainly includes non-in-situ artificial coating and in-situ artificial coating. For example, Chinese patent CN114551883A discloses a method for preparing a binder and titanic acid / titanate nanowire zinc negative electrode coating, comprising the following steps: (1) mixing NaOH solution with TiO 2 The nanoparticles are mixed to obtain a mixture; (2) the mixture is stirred evenly and subjected to a hydrothermal reaction; (3) the reaction product is centrifuged; (4) the reaction product is attached to the surface of the zinc negative electrode through a binder. Chinese patent CN117995972A discloses a method for preparing a zinc negative electrode modified with a zinc tungstate coating, comprising the following steps: (1) preparing a mixed solution of tungstate and ammonium fluoride; (2) placing the zinc negative electrode in the solution of step (1) to react and generate a protective layer; (3) taking out the electrode in step (2), washing it with deionized water and anhydrous ethanol for multiple times, and then drying it.

[0004] As mentioned above, these non-in-situ coatings are combined with zinc sheets through binders using inorganic or organic materials. This non-in-situ artificial coating can establish a relatively stable electrode / electrolyte interface to inhibit dendrites and side reactions on the surface of the zinc negative electrode. However, the thickness of the non-in-situ artificial coating is difficult to effectively control, which affects the Zn 2+ In addition, due to their poor interfacial contact with zinc, non-in-situ coatings are easily separated from the zinc surface during the cycle, and their role in inhibiting zinc dendrite growth and mitigating side reactions is limited. In-situ coatings mainly use acid or salt to etch the negative electrode surface to form a protective layer, which overcomes the problem of non-in-situ coatings being easily separated from zinc and effectively inhibits dendrite growth; however, single acid or salt etching causes the negative electrode to have poor ductility and is prone to breakage during the cycle, resulting in a reduced battery cycle life. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a preparation method and application of a protective detachment-resistant coating for the negative electrode of an aqueous zinc ion battery. The present invention uses organic acid + sodium citrate as the main raw materials, and constructs an in-situ protective detachment-resistant coating on a zinc sheet based on the "etching-nucleation growth" mechanism. The coating not only has good structural stability and is not easy to fall off, but also has a good protective effect on the zinc negative electrode, and can guide zinc ions to deposit uniformly on the surface of the zinc negative electrode, thereby inhibiting the formation of dendrites and improving the cycle life of the zinc negative electrode.

[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0007] First, the present invention provides a method for preparing a negative electrode protective detachment-resistant coating for an aqueous zinc ion battery, comprising the following steps:

[0008] Step 1: Clean the zinc sheet with dilute hydrochloric acid and anhydrous ethanol alternately.

[0009] Step 2: Mix and stir the sodium citrate and the organic acid solution to obtain a blended solution.

[0010] Step 3: Stir and heat the blended solution to perform a cross-linking reaction to obtain a viscous solution.

[0011] Step 4: Apply the viscous solution to the surface of the zinc sheet, and after the reaction, wash and dry to obtain an aqueous zinc ion battery negative electrode with a protective and resistant coating on the surface.

[0012] The present invention uses organic acid + sodium citrate as main raw materials, and constructs an in-situ protective and resistant peeling coating on a zinc sheet based on the "etching-nucleation growth" mechanism. Specifically:

[0013] (1) The protective layer constructed by the present invention has good structural stability and is not easy to fall off: first, the in-situ etching of the zinc sheet by organic acid generates an in-situ protective layer. Compared with the non-in-situ protective layer, the protective layer of the present invention grows on the zinc sheet and is not easily separated from the zinc surface during the zinc ion deintercalation process, thereby ensuring the integrity of the coating; second, the present invention can form a gel-like coating structure after the cross-linking reaction between organic acid and sodium citrate. Compared with a single organic acid or sodium citrate, the protective layer can maintain a stable structure during the zinc ion deintercalation process.

[0014] (2) The protective layer constructed by the present invention has a better effect on improving the performance of the zinc negative electrode: the etching of the organic acid protects the zinc metal from the side reactions caused by water, isolates the zinc metal from the electrolyte, and inhibits corrosion and hydrogen evolution reactions. The functional groups in sodium citrate have a strong adsorption effect on zinc ions, which can capture zinc ions in the solvent sheath, separate zinc ions from water molecules, promote the desolvation of zinc ions, reduce the resistance to zinc ion deposition, guide zinc ions to deposit uniformly on the surface of the zinc negative electrode, balance the electric field concentration, thereby inhibiting the formation of dendrites and improving the cycle life of the zinc negative electrode.

[0015] Preferably, in step 1, the concentration of the hydrochloric acid is 0.1 to 2 mol / L, and the cleaning time is 1 to 20 min.

[0016] Preferably, in step 2, the organic acid is selected from one or more of oxalic acid, tartaric acid, succinic acid, lactic acid, malic acid and fumaric acid; more preferably oxalic acid and tartaric acid, most preferably tartaric acid.

[0017] After the zinc negative electrode is etched by the above-mentioned organic acid surface, the surface (002) crystal plane accounts for a higher proportion. After the treatment, the zinc negative electrode exposes a more stable (002) crystal plane, which is conducive to the uniform deposition of zinc ions and slows down the formation of dendrites. The present invention further finds that different types of organic acids have different surface modification effects on the zinc negative electrode. For example, when the organic acid is oxalic acid, the surface of the coating formed is a dense brick-like structure and is distributed with irregular tunnels. This special morphology can increase the contact between the coating and the electrolyte and shorten the transmission distance of the zinc ions. When the organic acid is tartaric acid, the surface of the coating formed is a flat and dense layered structure. This structure increases the specific surface area of ​​the electrode, and the contact area between the negative electrode and the electrolyte is increased, which is more conducive to the transmission and deposition of zinc ions. In comprehensive comparison, oxalic acid has a better effect.

[0018] Preferably, in step 2, the concentration of the organic acid solution is 1-10 g / L; the mass ratio of the organic acid to sodium citrate is (1-4):1.

[0019] The present invention finds that the ratio of organic acid to sodium citrate is crucial. If the amount of organic acid added is too little, it will lead to a decrease in electronegative atoms, a decrease in the number of hydrogen bond donors, and insufficient cross-linking with sodium citrate, uneven etching of the zinc sheet, and the coating is very easy to fall off during the zinc plating and de-embedding process; on the contrary, if the amount of organic acid added is too much, it is easy to cause excessive etching, aggravating corrosion and hydrogen evolution reaction. The mass ratio of organic acid to sodium citrate used in the present invention is between just covering the surface of the zinc sheet and inhibiting the coating from falling off, so it can prevent the coating from falling off while inhibiting the occurrence of corrosion and hydrogen evolution reaction.

[0020] Preferably, in step three, the cross-linking reaction is carried out at a temperature of 15 to 70° C. for 1 to 24 hours.

[0021] The present invention finds that if the cross-linking reaction time is too short or the heating temperature is too low, the cross-linking reaction is likely to be insufficient and a uniform in-situ protective layer cannot be formed on the surface of the zinc sheet; if the reaction time is too long or the heating temperature is too high, the esterification reaction and hydrolysis will cause the destruction of the molecular structure and the change of properties, affecting the formation of the final cross-linked product, resulting in a decrease in the protective ability of the protective layer to the zinc negative electrode.

[0022] Preferably, in step 4, the coating method is drip coating, scraping coating or spin coating.

[0023] Preferably, in step four, the crystal plane of the aqueous zinc ion battery negative electrode having a protective anti-shedding coating on the surface is mainly (002) crystal plane; when the organic acid is oxalic acid, the surface of the protective anti-shedding coating has a dense brick structure and is distributed with irregular tunnels; when the organic acid is tartaric acid, the surface of the protective anti-shedding coating has a flat and dense layered structure.

[0024] Preferably, in step 4, the reaction time is 5 to 120 min; the coating film thickness is 10 to 150 μm; and the cleaning time is 1 to 10 min.

[0025] The present invention finds that the reaction time has an important influence on various properties of the coating. If the reaction time is too short, not only will the coating thickness be less than 10 μm, but the protective layer will also easily fall off the surface of the zinc negative electrode, and at the same time, the protection ability of the zinc sheet will be weakened; if the reaction time is too long, the coating thickness will exceed 150 μm, which will hinder the diffusion rate of zinc ions and reduce the battery capacity.

[0026] Secondly, the present invention provides an aqueous zinc ion battery negative electrode obtained by the above preparation method.

[0027] Finally, the present invention provides an aqueous zinc ion battery, whose negative electrode is the aqueous zinc ion battery negative electrode having a protective and anti-shedding coating on the surface obtained by the above preparation method.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] (1) The present invention uses organic acid + sodium citrate as the main raw materials, and constructs an in-situ protective and resistant-to-shedding coating on the zinc sheet based on the "etching-nucleation growth" mechanism. The coating not only has good structural stability and is not easy to fall off, but also has a good protective effect on the zinc negative electrode, and can guide zinc ions to deposit uniformly on the surface of the zinc negative electrode, thereby inhibiting the formation of dendrites and improving the cycle life of the zinc negative electrode.

[0030] (2) The coating preparation method of the present invention has the advantages of simple process, low cost and high safety, and is of great significance for promoting the commercial application of aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 X-ray diffraction patterns of the pure zinc foil of Comparative Example 1 and the oxalic acid / sodium citrate composite coating prepared in Example 1;

[0032] Figure 2 This is a scanning electron microscope image of the oxalic acid / sodium citrate composite coating prepared in Example 1;

[0033] Figure 3 This is a scanning electron microscope image of the tartaric acid / sodium citrate composite coating prepared in Example 2;

[0034] Figure 4 This is an optical photograph of the composite coating prepared in Comparative Example 2;

[0035] Figure 5 Optical photos of the electrodes of Example 1 and Comparative Example 1 after cycling;

[0036] Figure 6 This is a scanning electron microscope image of the oxalic acid / sodium citrate composite coating prepared in Comparative Example 3;

[0037] Figure 7 This is a scanning electron microscope image of the composite coating prepared in Comparative Example 4 without washing with hydrochloric acid and anhydrous ethanol;

[0038] Figure 8 This is a scanning electron microscope image of the oxalic acid / sodium citrate composite coating prepared in Comparative Example 5;

[0039] Fig. 9 This is a scanning electron microscope image of the oxalic acid / sodium citrate composite coating prepared in Comparative Example 6;

[0040] Fig.10 The symmetrical battery assembled with the zinc metal negative electrode modified with the oxalic acid / sodium citrate material prepared in Example 1 was -2 The current density and 1 mA·cm -2 Scanning electron microscope image of the negative electrode after cycling for 3000h at a deposition capacity of ;

[0041] Fig.11 For the symmetrical battery assembled with pure zinc foil in Comparative Example 1, at 1 mA·cm -2 The current density and 1 mAh cm -2 Scanning electron microscope image of the negative electrode after cycling for 120 hours at a deposition capacity of ;

[0042] Fig.12 The symmetric battery assembled with the zinc metal negative electrode modified with oxalic acid / sodium citrate material in which the amount of oxalic acid added in Comparative Example 2 was too small was -2 The current density and 1 mAh cm -2 Scanning electron microscope image of the negative electrode after cycling for 400 h at a deposition capacity of ;

[0043] Fig.13 A symmetrical battery assembled with the zinc ion battery negative electrode material in Example 1 was used at 1 mA·cm -2 The current density and 1 mAh cm -2 The voltage-time diagram obtained at the deposition capacity;

[0044] Fig.14 A symmetrical battery assembled with the zinc ion battery negative electrode material in Example 2 was used at 1 mA·cm -2 The current density and 1 mAh cm -2 The voltage-time diagram obtained at the deposition capacity;

[0045] Fig.15 For a symmetrical battery assembled with pure zinc foil in Comparative Example 1, at 1 mA·cm -2 The current density and 1 mAh cm -2 Time-voltage diagram obtained at the deposition capacity. DETAILED DESCRIPTION

[0046] The technical content and effects of the present invention are further described in detail below in conjunction with the embodiments, but the present invention is not limited thereto.

[0047] Comparative Example 1 (pure zinc sheet negative electrode)

[0048] (1) Use 1 mol / L dilute hydrochloric acid and anhydrous ethanol to repeatedly clean a 0.05 mm thick zinc sheet for 5 minutes to remove the oxide layer, grease and other impurities on the surface;

[0049] (2) The treated pure zinc sheet electrode material is cut into electrode discs with a diameter of 1.2 cm.

[0050] Comparative Example 2 (too little oxalic acid added)

[0051] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes (same as comparative example 1);

[0052] Step 2: Add 0.1 g of anhydrous oxalic acid into 100 ml of deionized water, stir to completely dissolve the oxalic acid, and obtain a 1 g / L oxalic acid aqueous solution; add 0.05 g of sodium citrate into the oxalic acid aqueous solution, and stir to obtain a blended solution;

[0053] Step 3: heating and stirring the blended solution at 60° C. for 2 hours, and the solution is cross-linked to form a viscous solution;

[0054] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet on one side, react for 15 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 50 μm. After drying at 70° C., a zinc metal negative electrode material with an oxalic acid / sodium citrate in-situ coating is obtained;

[0055] Step 5: Cut the zinc metal negative electrode material with the oxalic acid / sodium citrate in-situ coating into electrode discs with a diameter of 1.2 cm.

[0056] Comparative Example 3 (too much oxalic acid added)

[0057] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes;

[0058] Step 2: Add 1 g of anhydrous oxalic acid into 100 ml of deionized water, stir to completely dissolve the oxalic acid, and obtain a 10 g / L oxalic acid aqueous solution; add 0.25 g of sodium citrate into the oxalic acid aqueous solution, and stir to obtain a blended solution;

[0059] Step 3: heating and stirring the blended solution at 60° C. for 2 hours, and the solution is cross-linked to form a viscous solution;

[0060] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet on one side, react for 15 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 50 μm. After drying at 70° C., a zinc metal negative electrode material with an oxalic acid / sodium citrate in-situ coating is obtained;

[0061] Step 5: Cut the zinc metal negative electrode material with the oxalic acid / sodium citrate in-situ coating into electrode discs with a diameter of 1.2 cm.

[0062] Comparative Example 4 (Zinc sheet not cleaned with dilute hydrochloric acid and anhydrous ethanol)

[0063] Step 1: add 0.5 g of anhydrous oxalic acid into 100 ml of deionized water, stir to completely dissolve the oxalic acid, and obtain a 5 g / L oxalic acid aqueous solution; add 0.5 g of sodium citrate into the oxalic acid aqueous solution, and stir to obtain a blended solution;

[0064] Step 2: heating and stirring the blended solution at 60° C. for 2 hours, and the solution is cross-linked to form a viscous solution;

[0065] Step 3: Use a doctor blade method to apply the viscous solution on one side of the surface of the zinc sheet that has not been cleaned with hydrochloric acid and anhydrous ethanol, react for 15 minutes, rinse with deionized water for 2 minutes, and dry at 70° C. to obtain a zinc metal negative electrode material;

[0066] Step 4: Cut the zinc metal negative electrode material into electrode discs with a diameter of 1.2 cm.

[0067] Comparative Example 5 (reaction time after coating is too short, coating thickness is too thin)

[0068] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes;

[0069] Step 2: Add 0.9 g of anhydrous oxalic acid into 100 ml of deionized water, stir to completely dissolve the oxalic acid, and obtain a 9 g / L oxalic acid aqueous solution; add 0.3 g of sodium citrate into the oxalic acid aqueous solution, and stir to obtain a blended solution;

[0070] Step 3: heating and stirring the blended solution at 60° C. for 2 hours, and the solution is cross-linked to form a viscous solution;

[0071] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet on one side, react for 5 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 10 μm. After drying at 70° C., a zinc metal negative electrode material with an oxalic acid / sodium citrate in-situ coating is obtained;

[0072] Step 5: Cut the zinc metal negative electrode material with oxalic acid / sodium citrate coating into electrode discs with a diameter of 1.2 cm.

[0073] Comparative Example 6 (reaction time after coating is too long and coating thickness is too thick)

[0074] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes;

[0075] Step 2: Add 0.5 g of anhydrous oxalic acid into 100 ml of deionized water, stir to completely dissolve the oxalic acid, and obtain a 5 g / L oxalic acid aqueous solution; add 0.5 g of sodium citrate into the oxalic acid aqueous solution, and stir to obtain a blended solution;

[0076] Step 3: heating and stirring the blended solution at 60° C. for 2 hours, and the solution is cross-linked to form a viscous solution;

[0077] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet on one side, react for 120 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 150 μm. After drying at 70° C., a zinc metal negative electrode material with an oxalic acid / sodium citrate in-situ coating is obtained;

[0078] Step 5: Cut the zinc metal negative electrode material with oxalic acid / sodium citrate coating into electrode discs with a diameter of 1.2 cm.

[0079] Example 1

[0080] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes;

[0081] Step 2: Add 0.5 g of anhydrous oxalic acid into 100 ml of deionized water, stir to completely dissolve the oxalic acid, and obtain a 5 g / L oxalic acid aqueous solution; add 0.5 g of sodium citrate into the oxalic acid aqueous solution, and stir to obtain a blended solution;

[0082] Step 3: heating and stirring the blended solution at 60° C. for 2 hours, and the solution is cross-linked to form a viscous solution;

[0083] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet, react for 15 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 50 μm. After drying at 70° C., a zinc metal negative electrode material with an oxalic acid / sodium citrate in-situ coating is obtained;

[0084] Step 5: Cut the zinc metal negative electrode material with oxalic acid / sodium citrate coating into electrode discs with a diameter of 1.2 cm.

[0085] Example 2

[0086] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes;

[0087] Step 2: Add 0.3 g of tartaric acid into 100 ml of deionized water, stir to completely dissolve the tartaric acid, and obtain a 3 g / L tartaric acid aqueous solution; add 0.1 g of sodium citrate into the tartaric acid aqueous solution, and stir to obtain a blended solution;

[0088] Step 3: heating and stirring the blended solution at 60° C. for 3 hours, and the solution is cross-linked to form a viscous solution;

[0089] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet on one side, react for 15 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 50 μm. After drying at 70° C., a zinc metal negative electrode material with a tartaric acid / sodium citrate in-situ coating is obtained;

[0090] Step 5: Cut the zinc metal negative electrode material with tartaric acid / sodium citrate coating into electrode discs with a diameter of 1.2 cm.

[0091] Example 3

[0092] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes;

[0093] Step 2: Add 0.8 g of succinic acid into 100 ml of deionized water, stir to completely dissolve the succinic acid, and obtain an 8 g / L succinic acid aqueous solution; add 0.2 g of sodium citrate into the succinic acid aqueous solution, and stir to obtain a blended solution;

[0094] Step 3: heating and stirring the blended solution at 60° C. for 3 hours, and the solution is cross-linked to form a viscous solution;

[0095] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet on one side, react for 15 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 50 μm. After drying at 70° C., a zinc metal negative electrode material with a succinic acid / sodium citrate in-situ coating is obtained;

[0096] Step 5: Cut the zinc metal negative electrode material with the succinic acid / sodium citrate in-situ coating into electrode discs with a diameter of 1.2 cm.

[0097] Example 4

[0098] Step 1: Wash the zinc sheet with 1 mol / L dilute hydrochloric acid and anhydrous ethanol alternately for 5 minutes;

[0099] Step 2: Add 0.9 g of lactic acid into 100 ml of deionized water, stir to completely dissolve the lactic acid, and obtain a 9 g / L lactic acid aqueous solution; add 0.45 g of sodium citrate into the lactic acid aqueous solution, and stir to obtain a blended solution;

[0100] Step 3: heating and stirring the blended solution at 60° C. for 3 hours, and the solution is cross-linked to form a viscous solution;

[0101] Step 4: Use a doctor blade method to coat the viscous solution on one side of the zinc sheet, react for 15 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 50 μm. After drying at 70° C., a zinc metal negative electrode material with an in-situ lactic acid / sodium citrate coating is obtained;

[0102] Step 5: Cut the zinc metal negative electrode material with the lactic acid / sodium citrate in-situ coating into electrode discs with a diameter of 1.2 cm.

[0103] Example 5

[0104] Step 1: Use 1 mol / L dilute hydrochloric acid and anhydrous ethanol to clean the zinc sheet alternately;

[0105] Step 2: Add 1.0 g of malic acid into 100 ml of deionized water, stir to completely dissolve the malic acid, and obtain a 10 g / L malic acid solution; add 0.25 g of sodium citrate into the malic acid aqueous solution, and stir to obtain a blended solution;

[0106] Step 3: heating and stirring the blended solution at 60° C. for 3 hours, and the solution is cross-linked to form a viscous solution;

[0107] Step 4: Use a doctor blade method to apply the viscous solution to the surface of the zinc sheet on one side, react for 15 minutes, and then rinse with deionized water for 2 minutes to obtain an in-situ coating with a film thickness of about 75 μm. After drying at 70° C., a zinc metal negative electrode material with an in-situ coating of malic acid / sodium citrate is obtained;

[0108] Step 5: Cut the zinc metal negative electrode material with the malic acid / sodium citrate in-situ coating into electrode discs with a diameter of 1.2 cm.

[0109] Performance comparison

[0110] Table 1

[0111] Polarization voltage(V) Maximum cycle time (h) Comparative Example 1 0.15 120 Comparative Example 2 0.16 400 Comparative Example 3 0.10 450 Comparative Example 4 0.15 200 Comparative Example 5 0.12 400 Comparative Example 6 0.10 600 Example 1 0.05 3200 Example 2 0.07 2500 Example 3 0.07 1300 Example 4 0.08 1500 Example 5 0.05 1600

[0112] It can be seen from Table 1 that the composite coating of the present invention can provide better protection for the metal zinc negative electrode and prolong the service life. The concentration of the organic acid, the mass ratio of the organic acid to sodium citrate, the degree of crosslinking of the organic acid and sodium citrate, and the reaction time (film thickness) after coating of the organic acid and sodium citrate will affect the overall performance of the electrode material. Compared with bare zinc, the cycle period of the present invention is longer and the overall performance is better.

[0113] Depend on Figure 1 It can be seen that the oxalic acid / sodium citrate composite coating prepared in Example 1 has a higher proportion of the (002) crystal plane of the zinc negative electrode. After treatment, the zinc negative electrode exposes a more stable (002), which is conducive to the uniform deposition of zinc ions and slows down the formation of dendrites.

[0114] Depend on Figure 2 It can be seen that the oxalic acid / sodium citrate composite coating prepared in Example 1 has a uniform, dense brick-like surface and some irregular tunnels, which can increase the contact between the coating and the electrolyte and shorten the transmission distance of zinc ions.

[0115] Depend on Figure 3 It can be seen that the tartaric acid / sodium citrate composite coating prepared in Example 2 has a flat and dense layered surface. This structure increases the specific surface area of ​​the electrode, increases the contact area between the negative electrode and the electrolyte, and is more conducive to the transmission and deposition of zinc ions.

[0116] Depend on Figure 4 It can be seen that in Comparative Example 2, when too little oxalic acid was added, the coating became uneven and cracked. Too little oxalic acid resulted in insufficient reaction with the zinc surface, resulting in a weak coating.

[0117] Depend on Figure 5 It can be seen that the electrode sheet of the negative electrode of comparative example 1 is incomplete or even broken after cycling, and uneven dendrites appear on the surface; while after cycling, the negative electrode of embodiment 1 still maintains a complete and uniform structure, the surface is flat and free of dendrites, and the mechanical properties are greatly improved.

[0118] Depend on Figure 6 It can be seen that in Comparative Example 3, excessive addition of oxalic acid causes the surface structure of zinc to be damaged and corroded, resulting in loosely structured cracks and poor mechanical properties.

[0119] Depend on Figure 7 It can be seen that the zinc foil in Comparative Example 4 was not cleaned with hydrochloric acid and anhydrous ethanol, resulting in that the passivation layer on the zinc surface was not removed and the composite material could not adhere to the passivation layer.

[0120] Depend on Figure 8 It can be seen that the reaction time after coating of the composite material in Comparative Example 5 is too short and a dense structure cannot be generated. There are only some stripe-like protrusions on the zinc surface and the structure is incomplete, which makes the corrosion resistance of the coating worse.

[0121] Depend on Fig. 9 It can be seen that the reaction time after coating of the composite material in Comparative Example 6 is too long, which destroys the dense structure and causes uneven spherical particles to appear on the surface, which hinders the transmission of zinc ions.

[0122] Depend on Fig.10 It can be seen that after 3000 hours of cycling, the surface of the composite coating in Example 1 remains uniform without the generation of dendrites and side reaction products.

[0123] Depend on Fig.11 It can be seen that after 120 hours of cycling, a large amount of dendrites and side reaction products are generated on the surface of the pure zinc sheet of Comparative Example 1.

[0124] Depend on Fig.12 It can be seen that after 200 h of circulation, a large number of dendrites and side reaction products were generated on the surface of the composite material coating in Comparative Example 2 in which the amount of oxalic acid added was too small.

[0125] Depend on Figure 13-15It can be seen that, compared with Example 1-2 and Comparative Example 1, due to the optimization of zinc ion transport kinetics, the cycle stability of the zinc negative electrode containing the composite coating in the present invention is significantly improved, and the aqueous zinc ion battery achieves 3000h of continuous and stable operation. In addition, the overpotential of zinc deposition / stripping is reduced, thereby reducing the electrode polarization phenomenon and further enhancing the performance of the electrode.

[0126] The above embodiments of the present invention are merely examples for illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode protective detachment-resistant coating for an aqueous zinc ion battery, characterized in that: The steps include: Step 1: Clean the zinc sheet with hydrochloric acid and anhydrous ethanol alternately; Step 2: Mixing and stirring the sodium citrate and the organic acid solution to obtain a blended solution; Step 3: Stirring and heating the blended solution to perform a cross-linking reaction to obtain a viscous solution; Step 4: Apply the viscous solution to the surface of the zinc sheet, and after the reaction, wash and dry to obtain an aqueous zinc ion battery negative electrode with a protective and resistant coating on the surface.

2. The preparation method according to claim 1, characterized in that In step one, The concentration of the hydrochloric acid is 0.1-2 mol / L, The cleaning time is 1 to 20 minutes.

3. The preparation method according to claim 1, characterized in that: In step 2, the organic acid is selected from one or more of oxalic acid, tartaric acid, succinic acid, lactic acid, malic acid and fumaric acid.

4. The preparation method according to claim 1 or 3, characterized in that: In step 2, The concentration of the organic acid solution is 1 to 10 g / L; The mass ratio of the organic acid to sodium citrate is (1-4):

1.

5. The preparation method according to claim 1, characterized in that: In step three, the cross-linking reaction is carried out at a temperature of 15 to 70° C. for 1 to 24 hours.

6. The preparation method according to claim 1, characterized in that: In step 4, the coating method is drip coating, scraping coating or spin coating.

7. The preparation method according to claim 1, characterized in that: In step four, The reaction time is 5 to 120 minutes; The coating film thickness is 10-150 μm; The cleaning time is 1 to 10 minutes.

8. The preparation method according to claim 3, characterized in that: In step 4, the crystal plane of the aqueous zinc ion battery negative electrode having a protective and resistant-to-peeling coating on the surface is mainly (002) crystal plane; when the organic acid is oxalic acid, the surface of the protective and resistant-to-peeling coating has a dense brick-like structure and is distributed with irregular tunnels; when the organic acid is tartaric acid, the surface of the protective and resistant-to-peeling coating has a flat and dense layered structure.

9. A negative electrode for an aqueous zinc ion battery obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the negative electrode for an aqueous zinc ion battery obtained by the preparation method according to any one of claims 1 to 8 or the negative electrode for an aqueous zinc ion battery according to claim 9 in an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Aqueous zinc ion battery coating, negative electrode and battery

    CN114551883A

  • Zinc tungstate coating modified zinc negative electrode and preparation method and application thereof

    CN117995972A